Study histological alterations of the effect of Deltamethrin on the skin of the earthworm - Dhuha Talib Al-madani; Khadeeja AL_Khalidy (Al-Qadisiyah Journal of Pure Science, 2021)
Our study aims to investigate all the histological changes that occur in skin tissues of the earthworms that exposure to deltamethrin at concentration (1:2000) g/L. our study is included two groups, the first group exposed to deltamethrin at a concentration (12.5) mg/L while the second group is included normal earthworms (control group). The soil samples were collected from local agricultural land randomly in the Daghara district in the city of Diwaniyah, then adding deltamethrin by distributed to the collected soil samples equally. The experimental group is consists of (20) samples wherever, which showed that the histological changes of the skin of the earthworm that exposure to deltamethrin (12.5) mg/L is included breaking in the cuticle layer, with clear degeneration in the longitudinal and circular smooth muscle fibers. Furthermore, the sub-dermal layer is very thin and destroyed with clear degeneration of the epidermal cells as well as showed slight congestion of the blood vessels under the nerve and a clear breakdown of the cerebral nerve ganglia, while the control group consists of (20) soil samples collected randomly, wherever, demonstrates that the tissue of the skin of the earthworm was naturally without changes, as a normal cuticle layer is observed, the epidermis layer is lined with normal epithelial cells, and the smooth muscle layer appears naturally arranged. In a conclusion, deltamethrin has histopathological effects on skin tissues of the earthworms that make are destroyed and leading to negative effects on the earthworm.